Research on Modeling and Motion Optimization for an Underactuated Bionic Scorpion Robot Arm - Ning Cao; Jinsheng Liu; Feiling Shen; Xuming Pei; Yupu Liu; Hengyu Li (Applied Bionics and Biomechanics)
Flexible screen possessing a high-contrast ratio to accomplish high-definition display can be attributed to the accuracy of polarizer assembly. Different from the existing polarizer attached onto a flexible screen, resulting in low-accuracy and nonalignment attaching behaviors, a unique approach of underactuated bionic scorpion robot arms can be developed to explore the stable capture and accurate alignment motion operations. Overall structure design and D–H kinematic simulation of bionic scorpion robot arm can be conducted to analyze virtual three-key typical motions. Motion optimization of structural parameters and corresponding motion workspaces verification can be adopted to evaluate motion range and ability. Experiments can be utilized to verify the rationality of theoretical modeling and optimization simulation of bionic scorpion robot arm. Experimental results illustrate that it is evident to demonstrate that the motion behaviors of bionic scorpion robot arm can be verified to be consistent with three key states of virtual theoretical motions. The key joints possessing minor errors may also be utilized to illustrate the relatively excellent dynamic motions existing in bionic scorpion robot arm. Further, advancing the stable motion behaviors of bionic scorpion robot arm may solve the problems of low-accuracy and misalignment polarizer attachments.